Interleukin-4 differentially regulates osteoprotegerin expression and induces calcification in vascular smooth muscle cells - Hofbauer, Lorenz C.; Schrader, Jörg; Niebergall, Ute; Viereck, Volker; Burchert, Andreas; Hörsch, Dieter; Preissner, Klaus T.; Schoppet, Michael (Thrombosis and Haemostasis, 2006)
Vascular calcification is characterized by cellular transdifferentiation and expression of bone-related matrix proteins that result in the presence of bone-like structures in the vascular wall. Interleukin (IL)-4, a pleiotropic cytokine, and osteoprotegerin (OPG), an essential regulator of osteoclast biology, have both been linked to vascular disease. Here, we assessed the role of IL-4 and OPG in vascular calcification in vitro. IL-4 induced OPG mRNA levels and protein secretion by 5-fold in a dose-and time-dependent fashion in human coronary artery smooth muscle cells (CASMC). Activation of the transcription factor STAT6 preceded IL-4-induced OPG expression, and blockade of IL-4-induced STAT6 activation by the phospholipase C inhibitor D609 decreased OPG expression. Long-term exposure of IL-4 for 4 weeks resulted in transformation of CASMC towards an osteoblastic phenotype, based on the expression of the transcription factor Cbfa1 and increased mineral deposition. Notably, calcification of CASMC was inhibited by gene silencing of Cbfa1. During osteogenic transformation, IL-4 down-regulated OPG production in CASMC. IL-4 has differential effects in CASMC: While short-term exposure enhances OPG production through a STAT6-dependent mechanism, long-term exposure causes Cbfa1-dependent osteogenic transformation anda decreased production of OPG, an inhibitor of bone resorption.
Keywords: Cbfa1; interleukin-4; osteoprotegerin; smooth muscle cells; vascular calcification